Reforming Pensions : Myths, Truths, and Policy Choices - Barr, N. (IMF Working Papers; Working Paper ;, 2000)
This paper discusses the strategic building blocks of pension reform. The early sections set out the simple economics of pensions and discuss a series of myths which have proved remarkably persistent. Subsequent sections draw together the conclusions for policy design from earlier theoretical discussion, set out the prerequisites which any pension reform must respect, and discuss the range of choices facing policymakers. The main conclusions are threefold: the key variable is effective government; from an economic perspective the difference between PAYG and funding is second order; and the range of potential choice over pension design is wide.